2019
DOI: 10.3390/app9122577
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Applications of Optical Coherence Angiography Imaging in Ocular Vascular Diseases

Abstract: Optical coherence tomography angiography (OCTA) provides us with a non-invasive and efficient means of imaging anterior and posterior segment vasculature in the eye. OCTA has been shown to be effective in imaging diseases such as diabetic retinopathy; retinal vein occlusions; retinal artery occlusions; ocular ischemic syndrome; and neovascularization of the iris. It is especially useful with depth-resolved imaging of the superficial, intermediate, and deep capillary plexi in the retina, which enables us to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…However, fundus fluorescence angiography is not depth-resolved and therefore lacks the ability to distinguish the superficial from the DCP. 7…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, fundus fluorescence angiography is not depth-resolved and therefore lacks the ability to distinguish the superficial from the DCP. 7…”
Section: Discussionmentioning
confidence: 99%
“…However, fundus fluorescence angiography is not depth-resolved and therefore lacks the ability to distinguish the superficial from the DCP. 7 Studies have shown that OCTA has low intravisit and intervisit blood flow index and vascular density variability. 15,20 Our findings demonstrated that the macular and peripapillary retinal microvascular networks were significantly reduced in SLE patients with longer disease durations, compared with NCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation